The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1177/000313481107701018
|View full text |Cite
|
Sign up to set email alerts
|

Utilization and Outcomes of Laparoscopic Versus Open Paraesophageal Hernia Repair

Abstract: The optimal operative approach for repair of diaphragmatic hernia remains debated. The aim of this study was to examine the utilization of laparoscopy and compare the outcomes of laparoscopic versus open paraesophageal hernia repair performed at academic centers. Data was obtained from the University HealthSystem Consortium database on 2726 patients who underwent a laparoscopic (n = 2069) or open (n = 657) paraesophageal hernia repair between 2007 and 2010. The data were reviewed for demographics, length of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(25 citation statements)
references
References 13 publications
(17 reference statements)
1
22
0
2
Order By: Relevance
“…Although it is a technically challenging procedure, it has been proven to be safe and effective and is associated with excellent long-term patient outcomes in large reported series [15][16][17]. The procedure has the advantages of a minimally invasive approach, such as reduced postoperative pain, lower morbidity, and shorter hospital stay when compared to the open approach [18]. There are certain recognized pitfalls of laparoscopy, which include unstable video camera platform, limited motion (degrees of freedom) of straight laparoscopic instruments, two-dimensional imaging, and poor ergonomics for the surgeon [19].…”
Section: Discussionmentioning
confidence: 99%
“…Although it is a technically challenging procedure, it has been proven to be safe and effective and is associated with excellent long-term patient outcomes in large reported series [15][16][17]. The procedure has the advantages of a minimally invasive approach, such as reduced postoperative pain, lower morbidity, and shorter hospital stay when compared to the open approach [18]. There are certain recognized pitfalls of laparoscopy, which include unstable video camera platform, limited motion (degrees of freedom) of straight laparoscopic instruments, two-dimensional imaging, and poor ergonomics for the surgeon [19].…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic repair is associated with better outcomes compared with open repair, as measured by overall complication rates, hospital length of stay, cost, and readmission rate. 18 Multiple series have demonstrated that laparoscopic repair improves patient symptoms, including heartburn, regurgitation, chest pain, dysphagia, dyspnea, and overall quality of life. 17,19 Despite the superiority of laparoscopic repair, the long-term hernia recurrence rate exceeds 50% even in high-volume centers.…”
Section: Discussionmentioning
confidence: 99%
“…La mortalidad fue de 0.4% para la laparoscopia versus 0% para los abiertos. 20 Lo anterior está de acuerdo con nuestros resultados, donde tuvimos una estancia hospitalaria promedio de 3.68 días; ningún paciente requirió terapia intensiva; el porcentaje de complicaciones fue del 5 al 15%, todas ellas pulmonares, principalmente, sin readmisión a los 30 días.…”
Section: Discussionunclassified